Paranoia as an Antecedent and Consequence of Getting Ahead in Organizations: Time-Lagged Effects Between Paranoid Cognitions, Self-Monitoring, and Changes in Span of Control - Van Quaquebeke, Niels (Frontiers in Psychology, 2016)
A six-month, time-lagged online survey among 441 employees in diverse industries was conducted to investigate the role paranoia plays as an antecedent and as a consequence of advancement in organizations. The background of the study is the argument that it requires active social sense-making and behavioral adaptability to advance in organizations. The present paper thus explores the extent to which employees’ paranoid cognitions—representative of a heightened albeit suspicious sense-making and behavioral adaptability—link with their advancement in organizations (operationalized as changes in afforded span of control), both as an antecedent and an outcome. Following the strategy to illuminate the process by interaction analysis, both conditions (antecedent and outcome) are examined in interaction with employees’ self-monitoring, which is considered representative of a heightened but healthy sense-making and behavioral adaptability. Results support the expected interference interaction between paranoid cognitions and self-monitoring in that each can to some degree compensate for the other in explaining employees’ organizational advancement. Reversely, changes in span of control also affected paranoid cognitions. In particular, low self-monitors, i.e. those low in adaptive sense-making, reacted with heightened paranoid cognitions when demoted. In effect, the present study is thus the first to empirically support that paranoid cognitions can be a consequence but also a prerequisite for getting ahead in organizations. Practical advice should, however, be suspended until it is better understood whether and under what circumstances paranoia may relate not only to personally getting ahead but also to an increased effectiveness for the benefit of the organization.